Modern-day environmental factors in the pathogenesis of osteoarthritis. Issue 11 (November 2018) - Berenbaum, Francis; Wallace, Ian; Lieberman, Daniel; Felson, David
Abstract The prevalence of osteoarthritis (OA) is rising for reasons that are not fully understood. In this Opinion article, we review the possibility that OA is an evolutionary mismatch disease, which is a disease more common today than in the past because genes inherited from previous generations are inadequately or imperfectly adapted to modern environmental conditions. We focus on four major environmental factors in OA pathogenesis that have become ubiquitous within the past half-century: obesity, metabolic syndrome, dietary changes and physical inactivity. Because a cure for OA does not yet exist, prevention strategies that target these modifiable environmental factors are needed to curb further increases in OA prevalence. Environmental changes can sometimes be too rapid for genetic adaptation and result in a mismatch between our genetics and the environment. Osteoarthritis should be considered a mismatch disease owing to a rapid increase in prevalence that is associated with the modern lifestyle, diet and patterns of physical activity.